A composite slurry suitable for a sodium-ion battery separator, a coated slurry comprising the same, and a composite separator suitable for a sodium-ion battery
Patent Information
- Application Number
- CN202411742432.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-11-29
AI Technical Summary
问题一就是钠离子电池的循环寿命也有待提高
[0036]通过在电池隔膜端应用本申请的复合浆料,使得钠离子二次电池的循环寿命、充放电倍率得到显著改善。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of sodium-ion battery technology, and more particularly to a composite slurry suitable for sodium-ion battery separators, a coating slurry including the slurry, and a composite separator suitable for sodium-ion batteries. Background Technology
[0002] Sodium-ion batteries, a cutting-edge rechargeable battery technology, have become a major research hotspot in the field of energy storage. Although their working principle is quite similar to that of lithium-ion batteries, sodium-ion batteries have shown unique advantages in material selection and application areas. Their high efficiency, safety, and environmental friendliness give them enormous development potential in the future energy market. The core advantages of sodium-ion batteries lie in their abundant resources and low cost, making them highly sought after in large-scale applications such as new energy vehicles, energy storage systems, and smart grids.
[0003] However, sodium-ion batteries also face some shortcomings. One issue is the need to improve their cycle life. Cycle life refers to the number of times a battery can maintain stable performance during charge and discharge. During charge and discharge, the insertion and extraction of sodium ions causes changes in the structure of the electrode materials, thus affecting the battery's cycle stability. Although researchers are working to improve the cycle life of sodium-ion batteries by improving electrode materials and optimizing battery structure, this issue remains a significant factor restricting their widespread application.
[0004] Charge / discharge rate is another challenge facing sodium-ion batteries. Charge / discharge rate refers to the amount of electricity a battery can charge or discharge per unit of time. For applications requiring rapid charge / discharge, such as grid energy storage and emergency power supplies, the battery's charge / discharge rate is crucial. Because sodium ions diffuse relatively slowly, the charge / discharge rate of sodium-ion batteries is limited. Although improving the electrolyte and increasing the conductivity of electrode materials can improve the charge / discharge rate of sodium-ion batteries to some extent, there is still a long way to go before they reach the level of lithium-ion batteries.
[0005] Regarding sodium-ion battery separators, glass fiber membranes are typically used in laboratory development stages, while in commercial applications, polyolefin membranes used in lithium-ion batteries can be directly substituted for them. Because sodium electrolyte solvents differ, some dry-process and wet-process membranes require ceramic or other material coatings to improve the wettability of the sodium battery electrolyte to the separator. Furthermore, the SEI membrane formed in sodium-based electrolytes is often unstable due to the high solubility of its components. Since most inorganic sodiums present in the SEI membrane have higher solubility than their lithium analogues (NaF is more soluble than LiF, and Na₂CO₃ is more soluble than Li₂CO₃), the SEI membrane formed in conventional sodium batteries exhibits poor stability.
[0006] In view of this, the present invention is hereby proposed. Summary of the Invention
[0007] The purpose of this invention is to provide a composite slurry suitable for sodium-ion battery separators, a coating slurry including the slurry, and a composite separator suitable for sodium-ion batteries. By modifying the separator end, a composite separator that is more suitable for the current sodium-ion battery electrolyte system is developed, thereby improving the above-mentioned problems existing in current sodium-ion batteries and improving the cycle life and charge-discharge ratio of sodium-ion batteries.
[0008] To achieve the above objectives, the present invention adopts the following technical solution: A composite slurry suitable for sodium-ion battery separators, comprising, by mass fraction: 0-95% component A, 0-60% component B, 0-10% component C, 0-10% component D, with the balance being water and additives; Component A is a sodium salt that is sparingly soluble in water; preferably, component A includes one or more of the following: sodium bismuthate, sodium trititanate, sodium hexahydroxyantimonate, sodium uranyl zinc acetate, sodium trititanate, sodium hexafluorosilicate, sodium zirconate, sodium borate calcite, sodium metabismuthate, sodium H-acid monosodium = 1-amino-6-sulfonyl-8-naphthol-3-sulfonate, sodium antimonate, sodium uranate, and dipotassium sodium hexanitrite cobalt(III) nitrite; During battery formation, component A can provide initial sites for SEI film formation, further inducing its formation. The quantity and distribution of component A affect the final SEI film's density, uniformity, and stability. Unlike lithium-ion battery systems, conventional sodium-ion battery systems form SEI films primarily composed of NaF and Na₂CO₃. These two compounds exhibit poor stability in electrolytes compared to similar lithium compounds, making them prone to secondary dissolution and causing irreversible losses in capacity and cycle life. However, the passivation layer composite compound formed using component A as an initial site exhibits improved stability, along with better SEI film density, continuity, and uniformity, preventing other side reactions and self-discharge.
[0009] Component B is a sodium-containing complex; preferably, component B includes one or more of sodium aluminosilicate, sodium feldspar, and sodium metal-organic framework; Component B, containing sodium complex, has a certain degree of hardness and chemical inertness, as well as good high-temperature resistance. It is not easily decomposed at high temperatures and has significant inorganic metal oxide characteristics. The slurry coating constructed based on this not only has the function of assisting in the construction of SEI membrane, but also the coating structure formed can provide support for the diaphragm and improve the heat shrinkage resistance of the diaphragm material.
[0010] However, such substances have requirements on the molar mass of sodium. In component B, the molar mass ratio of non-sodium substances to sodium substances is preferably 1.5-5.0. If this ratio is too low, the proportion of sodium substances is too high, the component material is prone to hydrolysis, the instability is too high, and it cannot form a heat-resistant support coating. If this ratio is too high, the proportion of non-sodium substances is too high, the SEI film will be uneven during the electrochemical process, or it will not be able to effectively play its film-forming role.
[0011] When using component B, it is preferable to use a particle size D50 ≤ 1 μm; because if D50 is too high, the gaps between coating particles will be too large, resulting in poorer uniformity and causing unevenness in the SEI film.
[0012] The component C is a sodium-containing organic compound; preferably, the component C includes a sodium-containing organic compound with a carbon chain of 4 or more carbons and less than 12 carbons, or containing 8 or fewer methyl groups. More preferably, component C includes one or more of sodium ethoxide, sodium propoxide, sodium acetate, sodium propionate, sodium amino acid, sodium valerate, sodium 2,2-dimethylpropoxide, and saturated fatty acid salts; The primary function of component C is to assist in providing film-forming sites; secondly, when combined with other components, it can enhance the steric hindrance of the overall material, improve the suspension ability of particles, and enhance the stability of the system; at the same time, when combined with other slurries, it can enhance the flotation ability of the overall components, and after drying, the sodium-rich components are more likely to concentrate on the surface of the mixed coating.
[0013] The proportion of component C in the composite slurry should be ≤10wt%. Excessive content of component C can lead to unevenness of the SEI membrane in the system, and at the same time reduce the density and chemical stability of the SEI membrane, posing a risk of secondary decomposition of the SEI membrane.
[0014] Component D is a water-soluble sodium salt; preferably, component D includes: sodium bicarbonate, sodium hypophosphite, methyl orange, sodium fluorosilicate, sodium perborate, sodium lasaloxine, sodium monensin, and amaranth. Component D can firstly replenish the sodium content in the system. Sodium materials in soluble sodium salts are more likely to participate in the SEI membrane formation, which is more conducive to reducing the consumption of sodium elements in the electrolyte and has a sodium replenishment effect. Secondly, adding component D can make the sodium-containing components in the system carry a negative charge, thereby improving their dispersion effect in the slurry system.
[0015] Component D should be ≤10wt% in the composite slurry because the sodium element in component D is too reactive, which can easily lead to an increase in the water content of the coating and exacerbate the risk of side reactions. At the same time, component D is suitable as an auxiliary material for film formation, but not as the main material for film formation, because the stability of the SEI film generated with D as the site is worse than that generated with component A as the site, and it should not be added in large quantities.
[0016] The purity of components A, B, C and D must be ≥99.0%, and the particle size must be Dv10≥0.2um and Dv90≤4um. The additives include dispersants and / or antisettling agents; Wherein, components A, B, C and D are not all 0 at the same time.
[0017] Optionally, by mass fraction, the composite slurry comprises: 3-45% component A, 0-10% component C, 0-10% component D, with the balance being water and additives. Preferably, the composite slurry comprises: 3-45% component A, 0.5-4% component C, 0.1-4% component D, with the balance being water and additives.
[0018] This formulation is preferably suitable for application on existing polyolefin membranes or membrane coatings.
[0019] Na (a) X (b) Where Na represents Na atoms in the composite slurry formulation, a represents the number of Na atoms; X represents non-Na atoms in the composite slurry formulation, and b represents the sum of the numbers of non-Na atoms. Preferably, a / b ≥ 0.5 / 10; a further preferred a / b range is between 1 / 10 and 6 / 10. If the a / b value is too small, the coating cannot provide enough initial sites for SEI film formation, resulting in an insufficiently dense and unstable SEI film that is prone to collapse. If the a / b value is too high, Na, being a highly reactive element, easily absorbs water, increasing side reactions in the battery cell system.
[0020] Optionally, by mass fraction, the composite slurry comprises: 20-95% component A, 0-10% component C, 0-10% component D, with the balance being water and additives. This formulation is suitable as an additive, to be added to existing diaphragm coating slurries for doping and then used for coating. Na (a) X (b)Where Na represents Na atoms in the composite slurry formulation, a represents the number of Na atoms; X represents non-Na atoms in the composite slurry formulation, and b represents the sum of the number of non-Na atoms. This formulation preferably has a / b ≥ 2.5 / 10; this formulation is preferably used as an additive in conventional coating slurries; if the a / b value is too small, the added product cannot effectively improve SEI film formation.
[0021] Optionally, by mass fraction, the composite slurry comprises: 0-50% component A, 5-60% component B, 0-10% component C, 0-10% component D, with the balance being water and additives. This formulation can be applied directly to existing conventional diaphragms or coatings, or used as an additive to existing conventional slurries.
[0022] Na (a) X (b) Where Na represents Na atoms in the composite slurry formulation, a represents the number of Na atoms; X represents non-Na atoms in the composite slurry formulation, and b represents the sum of the numbers of non-Na atoms. The preferred formulation has a / b ≥ 0.25 / 10, while the molar ratio of non-sodium to sodium substances in the system is between 1.5 and 5.0. a / b ≥ 0.25 / 10 ensures the coating provides sufficient initial sites, while the molar ratio of non-sodium to sodium substances between 1.5 and 5.0 primarily ensures the chemical and thermal stability of the coating material, improves environmental tolerance, and guarantees heat resistance.
[0023] This invention also provides a coating slurry suitable for sodium-ion battery separators, the coating slurry comprising the aforementioned composite slurry; the preparation method of the coating slurry includes method one and method two: Method one includes: S1: Mix the dispersant, anti-settling agent and water, stir until a clear solution is obtained, and add components A, B, C and D to the clear solution in a certain ratio to obtain the dispersion, which is the composite slurry; S2: Dilute the dispersion obtained in S1 with pure water to a solid content of 3-40 wt%, and then add adhesive one and wetting agent in sequence to obtain the coating slurry; Preferably, the composite slurry in Method 1 comprises: 3-45% component A, 0-10% component C, 0-10% component D, and the remainder is water and additives; Alternatively, the composite slurry in Method 1 may comprise: 0-50% component A, 5-60% component B, 0-10% component C, 0-10% component D, with the remainder being water and additives; The second method includes: S1: Mix the dispersant, anti-settling agent and water, stir until a clear solution is obtained, and add components A, B, C and D to the clear solution in a certain ratio to obtain the dispersion, which is the composite slurry; S2: Add adhesive two to the dispersion obtained in S1; preferably, the amount of adhesive two is 0-2 wt% of the coating slurry; S3: The mixture obtained in S2 is added as an additive to the precursor coating slurry, and the amount of the additive is 2-20 wt% of the precursor coating slurry; the precursor coating slurry includes organic coating slurry and inorganic coating slurry.
[0024] The organic coating slurry is preferably an adhesive coating slurry with polymers including PVDF and PMMA as the main materials; the inorganic coating slurry is preferably a heat-resistant coating slurry with alumina or boehmite as the main materials. The composite slurry prepared by method two of the present invention is equivalent to an additional additive to a slurry and can be used in any known or unknown coating slurry.
[0025] Preferably, the amount of component B used in method two is 0; More preferably, the composite slurry in Method 2 comprises: 20-95% component A, 0-10% component C, 0-10% component D, and the balance being water and additives.
[0026] The dispersant is selected from one or more of ammonium polycarboxylate, sodium polycarboxylate, polyacrylate, and phosphate ester; the amount of the dispersant added is 0.5-5 wt% of the dispersion. The anti-settling agent is selected from one or more of sodium carboxymethyl cellulose, cellulose, PVP, block copolymers of polyurethane, polyacrylate copolymers, and polyvinylpyrrolidone; the amount of the anti-settling agent added is 0.5-5 wt% of the dispersion. The adhesive one comprises one or more of the following: emulsion-type acrylate polymer, solution-type acrylate polymer, polyurethane polymer, polyacrylamide polymer, polyimide polymer, and polyamide polymer; the amount of the adhesive one added accounts for 1-20 wt% of the obtained coating slurry; The wetting agent includes one or more of the following: organosilicon-modified wetting agent, polyether wetting agent, alkynyl alcohol wetting agent, and alcohol wetting agent; the amount of the wetting agent added accounts for 0.01-2.5% of the obtained coating slurry; The second adhesive can be the adhesive in the precursor coating slurry, or one or more of the following: emulsion-type acrylate polymer, solution-type acrylate polymer, polyurethane polymer, polyacrylamide polymer, polyimide polymer, and polyamide polymer.
[0027] Preferably, after step S1 and before step S2, the method further includes: adding a hydrophobic additive to the dispersion for modification and / or grinding the dispersion using a sand mill; The hydrophobic additive includes a coupling agent and a hydrophobic polymer. The modification includes: adding a coupling agent and a hydrophobic polymer to the obtained dispersion, dispersing them evenly, and then keeping them at 30-70℃ for 2-4 hours to carry out hydrophobic modification. The coupling agent is selected from one or more of the following: organochromium complexes, silanes, titanates, and aluminates; The hydrophobic polymer is selected from one or more of the following: olefin-modified polymers containing hydrophobic groups, acrylonitrile polymers, acrylate polymers, and methacrylate polymers. The amount of hydrophobic additive added is 0.5-5 wt% of the dispersion; Preferably, the amount of the coupling agent added is 0-2 wt% of the dispersion; By performing hydrophobic modification and grafting modification on the surface, the original hydrophilic groups on the surface of the component are consumed, making it hydrophobic as a whole in the end. The diameter of the zirconium balls in the sand mill is 500-1000 times the particle size of components A, B, C, and D. Sand milling can make the components in the system more uniformly dispersed and modified, improve the overall consistency of the system, and prevent the agglomeration of large particles, which could lead to sodium precipitation in the product.
[0028] The present invention also provides a composite separator suitable for sodium-ion batteries, the composite separator comprising a separator substrate and the coating slurry provided by the present invention coated on the surface of the separator substrate.
[0029] The method for preparing the composite separator includes: coating a separator substrate with a coating slurry prepared using the composite slurry provided by the present invention to form a composite separator. The coating surface can be the positive electrode side, the negative electrode side, or both positive and negative electrodes. Each coating of the composite separator contains the slurry provided by the present invention. The membrane is then dried and wound to obtain the composite separator suitable for sodium-ion batteries. The separator substrate includes any one of wet-process polyolefin porous membranes, dry-process polyolefin porous membranes, spun composite porous membranes, and non-woven porous membranes.
[0030] Optionally, the coating method can be any one of gravure roller coating, anilox roller coating, spraying, dot coating, dip coating, slot coating, or screw extrusion coating.
[0031] During the drying process, the oven temperature range is 40-90℃.
[0032] This application also provides a sodium-ion secondary battery prepared using the composite separator provided in this application, which is suitable for sodium-ion batteries, and further includes a positive electrode, a negative electrode, and an electrolyte.
[0033] This application also provides a battery module, which includes the sodium-ion secondary battery provided in this application.
[0034] This application also provides a battery pack, which includes the battery module provided in this application.
[0035] This application also provides an electrical device, which includes one or more combinations of the sodium-ion secondary battery, the battery module, and the battery pack provided in this application.
[0036] By applying the composite slurry of this application to the battery separator, the cycle life and charge / discharge rate of sodium-ion secondary batteries are significantly improved.
[0037] The composite slurry and coating slurry provided in this application can be used to prepare composite separators by coating them onto currently commercially available separators, or by coating them onto other substrates to obtain composite separators. These methods improve the wettability of the electrolyte, preventing further reactions between the electrolyte and electrode materials, thereby reducing the consumption of electrolyte and electrode materials by more than 90%. The improved interfacial compatibility between the separator, electrolyte, and electrode materials results in more uniform sodium ion transport and lower impedance throughout the interface, increasing the sodium ion diffusion rate and significantly improving the charge / discharge rate, thus enhancing the rate performance and cycle life of secondary sodium batteries.
[0038] The SEI film formed by this application is denser and has higher stability in the electrolyte. Its components will not dissolve again in the electrolyte, and will not cause capacity decay and cycle performance loss at the product design level.
[0039] Compared with the prior art, the present invention has the following beneficial effects; The composite slurry provided in this application provides initial sites for SEI film growth and induces the SEI to form a denser layer structure, preventing further reaction between the electrolyte and electrode materials. This reduces the consumption of electrolyte and electrode materials by more than 90%, reduces the loss of energy density in sodium-ion batteries, and improves battery capacity and cycle performance.
[0040] The coating slurry prepared using the composite slurry provided in this application has higher stability in the electrolyte. Its components will not dissolve again in the electrolyte, and will not cause capacity decay and cycle performance loss at the product design level, resulting in higher capacity retention rate of sodium batteries after long cycles.
[0041] The composite separator provided in this application has better compatibility between the separator coating and the electrolyte, which guides sodium ions to be deposited uniformly at the negative electrode interface, making the sodium ion distribution at the interface more uniform. This results in more uniform sodium ion transport throughout the interface and lower impedance, thereby increasing the sodium ion diffusion rate and significantly improving the charge and discharge rate. At the same time, it improves the wettability of the electrolyte, with the contact angle between the sodium ion battery electrolyte and the separator being ≤30°. The wettability is more than 200% higher than that of conventional polyolefin dry-process membrane substrates, more than 100% higher than that of conventional polyolefin wet-process membrane substrates, and more than 50% higher than that of conventional ceramic-coated composite membranes. Detailed Implementation
[0042] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0043] Example 1 This embodiment provides a composite slurry suitable for sodium-ion battery separators, comprising, by mass fraction: 5% sodium calcite borate, 4% sodium zinc uranyl acetate, 1% sodium valerate, 0.5% sodium bicarbonate, appropriate amounts of ammonium polycarboxylate, sodium carboxymethyl cellulose, and water. (a) X (b) The a / b value ranges from 3 to 4 / 10. Among them, the final overall Dv50 particle size ranges from 0.2 to 0.4 μm for sodium borate calcite, sodium uranyl zinc acetate, sodium valerate, and sodium bicarbonate. This embodiment also provides a coating slurry comprising the composite slurry and the resulting composite membrane, the preparation steps of which are as follows: S1: Mix the polycarboxylate ammonium salt (0.5% by mass), sodium carboxymethyl cellulose (0.5% by mass), and water (the remainder by mass) and stir until a clear solution is obtained. Add 5% sodium borate calcite, 4% sodium uranyl zinc acetate, 1% sodium valerate, and 0.5% sodium bicarbonate to the clear solution to obtain the dispersion, which is the composite slurry. S2: Dilute the dispersion obtained in S1 with pure water to a solid content of 6 wt%, then add 1 wt% of emulsion-type acrylate polymer and 0.04 wt% of organosilicon-modified wetting agent in sequence to obtain the coating slurry; S3: The coating slurry prepared in S2 is coated on one side of a 9μm thick polyolefin separator substrate with a coating thickness of 1.0μm. After drying at 60℃, it is wound up to obtain a composite separator suitable for sodium-ion batteries.
[0044] Example 2 This embodiment provides a composite slurry suitable for sodium-ion battery separators, comprising, by mass fraction: 4% sodium bismuthate, 3% sodium trititanate, 1% sodium valerate, 0.5% sodium bicarbonate, ammonium polycarboxylate (0.5% by mass), sodium carboxymethyl cellulose (0.2% by mass), and water (the balance by mass). After compounding, Na... (a) X (b) The a / b value ranges from 5 to 6 / 10. Among them, the particle size of sodium bismuthate, sodium trititanate, sodium valerate, and sodium bicarbonate is 0.2-0.5 μm. This embodiment also provides a coating slurry comprising the composite slurry and the resulting composite membrane, the preparation steps of which are as follows: S1: Mix ammonium polycarboxylate (0.5% by mass), sodium carboxymethyl cellulose (0.2% by mass), and water (the remainder by mass) and stir until a clear solution is obtained. Add 5% sodium borate calcite, 4% sodium uranyl zinc acetate, 1% sodium valerate, and 0.5% sodium bicarbonate to the clear solution to obtain the dispersion, which is the composite slurry. S2: Dilute the dispersion obtained in S1 with pure water to a solid content of 10 wt%, then add 2 wt% of emulsion-type acrylate polymer and 0.06 wt% of organosilicon-modified wetting agent in sequence to obtain the coating slurry; S3: The coating slurry obtained in S2 is coated on one side of the separator substrate, wherein the separator substrate is a polyolefin separator with a ceramic coating on its surface, wherein the ceramic coating thickness is 2μm, the polyolefin separator itself thickness is 9μm, the coating thickness of the coating slurry provided in this application is 1.0μm, and then dried at 60℃ and wound up to obtain a composite separator suitable for sodium-ion batteries.
[0045] Example 3 Several composite slurries, coating slurries, and composite membranes are provided using the same or similar methods as in Examples 1 or 2, with specific formulations and parameters shown in Table 1 below: Table 1. Composite slurry formulation and composite membrane parameters for Examples 3-4 Comparative Example 1 This comparative example is a PE base film with a thickness of 9μm.
[0046] Comparative Example 2 This comparative example is a diaphragm formed by coating a 3μm ceramic coating on one side of a 9μm thick PE base film.
[0047] The separators provided in the examples and comparative examples were used in sodium-ion batteries for performance testing: 1. Cyclic performance test conditions: Capacity retention rate after 1500 cycles at 2.0-3.8V; Test method: Under normal temperature conditions, use a charge-discharge cycle tester to perform 1500 charge-discharge cycles at 2.0-3.8V and record the capacity retention rate. 2. Low-temperature discharge performance evaluation parameters: -10℃ 1C capacity retention rate; Test method: The battery is placed in a specific low-temperature environment for cooling to -20℃. Then, a charge-discharge cycle tester is used to discharge the battery under a constant current of 1C, and its capacity retention rate is recorded. 3. Rate Discharge Evaluation Standard: 3C Capacity Retention Rate at Room Temperature; Test Method: In a room temperature environment, use a charge-discharge cycle tester to discharge the battery under a constant current of 3C and record its capacity retention rate.
[0048] The specific test results are shown in Table 2 below: Table 2 contains the sodium-ion battery performance test tables for the separators provided in the examples and comparative examples. As shown in Table 2, comparing Examples 1-4 with Comparative Examples 1 and 2, the separators prepared from the slurry in Examples 1-4 significantly improve the initial coulombic efficiency, cycle performance, low-temperature discharge, and rate discharge performance of sodium-ion batteries. Products with added sodium-rich coatings or coatings containing sodium-rich materials exhibit a significantly reduced contact angle between the coating and the electrolyte, indicating improved hydrophilicity of the coating. The application of sodium-rich materials in the separator significantly improves the poor electrical performance issues currently faced by sodium battery systems.
[0049] Examples 1-4 describe sodium-rich material coatings with component A as the main material and the remaining components as auxiliary materials. This coating is thin but provides more and more stable initial sites, resulting in a denser and more uniform SEI film with higher stability, thus leading to optimal electrochemical performance. However, this coating does not improve heat resistance.
[0050] The slurry composition provided in this application offers initial sites for SEI film growth and induces a denser SEI layer structure, preventing further reactions between the electrolyte and electrode materials. This reduces the consumption of electrolyte and electrode materials, resulting in more stable coulombic efficiency in sodium batteries over long cycles. Furthermore, the dense, chemically stable, and electrochemically resistant SEI film structure formed in this application solves the problems of low stability, easy secondary dissolution, and discontinuity in SEI films formed in traditional sodium-ion batteries. This significantly improves the cycle life, low-temperature discharge capability, and high-rate discharge capability of sodium-ion batteries.
[0051] Please note that the technical features of the above embodiments can be combined arbitrarily. For the sake of brevity, not all possible combinations of the technical features in the above embodiments have been described. However, as long as the combination of these technical features does not contradict each other, it should be considered within the scope of this specification. The above embodiments only illustrate several implementation methods of this application, and their descriptions are relatively specific and detailed, but they should not be construed as limiting the scope of the invention patent. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.
Claims
1. A composite slurry suitable for sodium-ion battery separators, characterized in that, The composite slurry comprises, by mass fraction: 3-45% component A, 0-60% component B, 0.5-4% component C, 0.1-4% component D, with the balance being water and additives; The additives include dispersants and / or antisettling agents; Component A is one or more of sodium bismuthate, sodium uranyl zinc acetate, sodium calcite borate, sodium uranate, and sodium dipotassium hexanoate cobalt(III) nitrite. Component B is one or more of sodium aluminosilicates and sodium metal-organic frameworks; Component C is one or more of sodium ethoxide, sodium propoxide, sodium acetate, sodium propionate, sodium amino acid, sodium valerate, and sodium 2,2-dimethylpropoxide. Component D is sodium bicarbonate; In the composite slurry, Na (a) X (b) Where Na represents Na atoms in the composite slurry formulation, a represents the number of Na atoms; X represents non-Na atoms in the composite slurry formulation, b represents the sum of the number of non-Na atoms, and a / b ranges from 1 / 10 to 6 / 10. The final overall Dv50 particle size range of components A, B, C, and D is 0.
2. 0.4μm.
2. A coating slurry suitable for sodium-ion battery separators, characterized in that, The coating slurry includes the composite slurry as described in claim 1.
3. The coating slurry according to claim 2, characterized in that, The preparation method of the coating slurry includes method one or method two: The first method includes: S1: Mix the dispersant, anti-settling agent and water, stir until a clear solution is obtained, and add components A, B, C and D to the clear solution in a certain ratio to obtain the dispersion, which is the composite slurry; S2: Dilute the dispersion obtained in S1 with pure water to a solid content of 3-40 wt%, and then add adhesive one and wetting agent in sequence to obtain the coating slurry; The second method includes: S1: Mix the dispersant, anti-settling agent and water, stir until a clear solution is obtained, and add components A, B, C and D to the clear solution in a certain ratio to obtain the dispersion, which is the composite slurry; S2: Add adhesive II to the dispersion obtained in S1; S3: The mixture obtained in S2 is added as an additive to the precursor coating slurry, and the amount of the additive is 2-20 wt% of the precursor coating slurry; the precursor coating slurry includes organic coating slurry or inorganic coating slurry.
4. The coating slurry according to claim 3, characterized in that, The dispersant is selected from one or more of ammonium polycarboxylate, sodium polycarboxylate, polyacrylate, and phosphate ester; the amount of the dispersant added in either method one or method two accounts for 0.5-5 wt% of the dispersion. The anti-settling agent is selected from one or more of sodium carboxymethyl cellulose, cellulose, block copolymers of polyurethane, polyacrylate copolymers, and polyvinylpyrrolidone; the amount of the anti-settling agent added in either method one or method two accounts for 0.5-5 wt% of the dispersion. The adhesive one comprises one or more of the following: emulsion-type acrylate polymer, solution-type acrylate polymer, polyurethane polymer, polyacrylamide polymer, polyimide polymer, and polyamide polymer; the amount of the adhesive one added accounts for 1-20 wt% of the obtained coating slurry; The wetting agent includes one or more of organosilicon-modified wetting agents, polyether wetting agents, and alcohol wetting agents; the amount of the wetting agent added accounts for 0.01-2.5% of the obtained coating slurry; The second adhesive includes one or more of the following: emulsion-type acrylate polymers, solution-type acrylate polymers, polyurethane polymers, polyacrylamide polymers, polyimide polymers, and polyamide polymers.
5. The coating slurry according to claim 3, characterized in that, After step S1 and before step S2, the method further includes: adding a hydrophobic additive to the dispersion for modification and / or grinding the dispersion using a sand mill. The hydrophobic additive includes a coupling agent and a hydrophobic polymer. The modification includes: adding a coupling agent and a hydrophobic polymer to the obtained dispersion, dispersing them evenly, and then keeping them at 30-70℃ for 2-4 hours to carry out hydrophobic modification. The coupling agent is selected from one or more of the following: organochromium complexes, silanes, titanates, and aluminates; The hydrophobic polymer is selected from one or more of the following: olefin-modified polymers containing hydrophobic groups, acrylonitrile polymers, acrylate polymers, and methacrylate polymers. The amount of hydrophobic additive added is 0.5-5 wt% of the dispersion; The coupling agent is added at a concentration of 0-2 wt% of the dispersion. The diameter of the zirconium balls in the sand mill is 500-1000 times the particle size of components A, B, C, and D.
6. A composite separator suitable for sodium-ion batteries, characterized in that, The composite diaphragm includes a diaphragm substrate and a coating slurry as described in any one of claims 2-5 coated on the surface of the diaphragm substrate.
Citation Information
Patent Citations
NaF / metal composite sodium-supplementing positive electrode active material, positive electrode material, positive electrode, preparation of positive electrode and application of positive electrode in sodium-ion battery
CN111293288A
Composite coating sodium-ion battery diaphragm and preparation method thereof
CN113675533A